Direct Investment (FDI) on Economic Growth in Nepal - Basnet, Naresh (Journal of Rapti Babai Campus, 2026)
Foreign Direct Investment (FDI) is particularly relevant and catalytic in this connection, standing as it does within the web connecting domestic and international capital flows and sophisticated technologies and management and access to the global marketplace, particularly in the context of those economies still struggling under the huge burden of achieving economic development. As foreign direct investment (FDI) into Nepal is desirable but not compulsory for achieving ambitious development gains in a low-income, encapsulated economy crippled with domestic capital inadequacies, attracting solid and sustained FDI into Nepal is in every ontological sense, welcome news, and not only for the consubstantial, either. Method In this study the cause and effect connection has been assessed through detail oriented research paper by undertaking scrupulous empirical investigation to discover the impact of Foreign Direct Investment (FDI) on Economic Growth reflected through the advancement rate of the GDP of Nepal for a long time period of time from 2000–20023. The study is quantitative where the larger set of data has been used from the reliable sources of literature ie: Nepal Rastra bank, World Bank & Ministry of Finance. Using a multivariate OLS regression model, we provide an in-depth examination of the statistical correlation between FDI inflows and its major macroeconomic variables including inflation and trade-openness and their cumulative impact on the Nepalese growth story.